ANALISA KELENGKAPAN RESEP SECARA ADMINISTRATIF DAN FARMASETIK DI APOTEK LIFEPACK JAKARTA - Aripin; Honey Iskandar; Vonny Nofrika; Sella Sellia (Jurnal Farmasi IKIFA, 2024)
Law Number 36 of 2009 concerning health states that pharmaceutical practice includes manufacture, including quality control of pharmaceutical preparations, security, procurement, storage, and distribution of drugs, service of prescription drugs, drug information services, and development of drugs, medicinal ingredients, and traditional medicines. carried out by health workers who have the expertise and authority to do so in accordance with the provisions of laws and regulations. Problems in prescribing, such as incomplete patient information, writing prescriptions that are unclear or even illegible, errors in writing dosages, not including drug usage rules, not writing down the route of drug administration, and not including signatures or initials for writing prescriptions, are problems that can cause medication errors. The research objective was to determine the administrative completeness and suitability of prescription pharmaceuticals at the Jakarta Lifepack Pharmacy in accordance with Minister of Health Regulation No. 73 of 2016. In this research paper, a quantitative descriptive method is used, namely a method used to describe a situation in a systematic, factual, and accurate manner. To describe a situation that would later become an article, a field observation was carried out at the Lifepack Pharmacy in Jakarta. The results of the study were administrative completeness of the prescription in the aspects of patient name 100%, patient age 91%, gender 52%, body weight 38%, doctor's name 100%, SIP 100%, doctor's address 100%, doctor's signature 36%, and prescription date 100%. Complete prescription pharmaceutically in terms of dosage form (98%), dosage strength (100%), and method of use (100%). The conclusion of the research is that the percentage of administratively complete prescriptions is 23.62%, and pharmaceutically, it is 98.06%.